Hepatocellular carcinoma escapes immune surveillance through deceiving thymus into recalling peripheral activated CD8+ T cells - Qiaoting Hu; Xuefeng Wang; Yundan You; Jun Liu; Bin Lan; Fangfang Chen; Hong Wen; Haili Cheng; Weibin Zhuo; Ting Xu; Jingxian Zheng; Yuchuan Jiang; et al. (Neoplasia: An International Journal for Oncology Research)
The role of thymic epithelial cells (TECs) in eliminating self-reactive T cells through the presentation of self-antigens is well-established. However, it remains unclear whether TECs can eliminate tumor-reactive CD8+ T cells by presenting tumor antigens. In this study, we observed that CD73+ Granzyme B+ peripheral activated CD8+ T cells undergo apoptosis in the medullary region of the thymus in DEN-CCL4-induced spontaneous HCC mice, but not in the naïve control group. Mechanistically, HCC cells manipulate the thymus to recruit peripheral activated CD8+ T cells through the CCL19/CCL21-CCR7 axis. Additionally, TECs capture antigens from HCC cells for subsequent antigen presentation instead of de novo expressing tumor antigens. When tumor-associated CD8+ T cells homing to the thymus recognize the same tumor antigen presented by TECs, activation-induced cell death (AICD) is initiated in these T cells. Thymectomy redistributes CD8+ T cells into the tumor focus to suppress HCC growth. Alternatively, both inhibiting CCL19/CCL21 expression of thymic cells using an AMPK activator and blocking CCR7 on CD8+ T cells binding with ligands using Cmp2105 significantly reduces tumor-educated thymus dependent immune evasion. Our findings collectively demonstrate that HCC manipulates the thymus to trigger immune escape; pharmacologically targeting CCL19/CCL21-CCR7 axis to inhibit thymus homing can increase CD8+ T cells in the tumor microenvironment.